Go International's Strategy On East Java Handicraft MSMES: A Case Study In The Creative Industry - Afif Nur Rokhman; Sudarmiatin; Heri Pratikto (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to analyze the strategy of going international in Micro, Small, and Medium Enterprises (MSMEs) in the handicraft sector in East Java with a case study approach on Written Batik MSMEs "Sumber Rejeki" in Sidoarjo Regency. The background of this research is based on the increasing demands of globalization and international market opportunities for the local creative industry, but still faced with limited capacity, market access, and digital literacy. The research method uses a qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. Data analysis was carried out descriptively with the theoretical framework of internationalization strategy and resource-based view (RBV). The results of the study show that the go international strategy implemented includes: (1) the use of global digital and e-commerce platforms as a means of penetrating the international market, (2) strengthening branding based on local wisdom through storytelling of batik products, (3) participation in international exhibitions and government programs such as trade expos, and (4) collaboration with export partners and aggregators. However, MSMEs still face various challenges, such as limited production capacity, international quality standards, logistical constraints, and export regulations. This research implies that the success of the internationalization of MSMEs is not only determined by internal resources, but also by ecosystem support, including governments, digital platforms, and global business networks.